A heterotopic pregnancy at 12 weeks pregnancy - Suhandri, Wiwin; Riandi, Diki (International Surgery Journal, 2024)
Heterotopic pregnancy (HP) represents a rare and complex condition where simultaneous pregnancies occur at different implantation sites, with only one located within the uterine cavity. Typically diagnosed in the first trimester, HP presents diagnostic challenges due to its rarity and varying clinical presentations. Here, we present a unique case of HP diagnosed at Bengkalis Hospital involving a 42-year-old multipara at 12 weeks of gestation. The patient’s presentation included regular uterine contractions and upper abdominal pain, with a positive Plano test upon admission. Despite experiencing vaginal bleeding two days prior and an initial refusal of care, further examination revealed a 2.13 cm gestational sac in the intrauterine cavity, consistent with the gestational age. Additionally, free intra-abdominal fluid was observed in the Douglas cavity. Haematological examination indicated a low haemoglobin level of 7.2 g/dl and elevated leukocytes at 16,000. An emergency laparotomy revealed a ruptured right ovarian tube containing a gestational sac, which was managed with hemostasis and a subsequent salpingectomy. The left ovarian tube underwent a tubectomy as a preventive measure. The patient received multiple blood transfusions, leading to an improvement in haemoglobin levels to 10.2 g/dl postoperatively. Following a two-day hospitalisation, the patient was discharged in good general condition. HP cases often necessitate laparotomies for tubal pregnancies, and ultrasound plays a crucial role in diagnosis, especially given its prevalence of 1 in 7000 due to assisted reproduction. Treatment typically involves laparoscopic or laparotomic intervention, highlighting the multidisciplinary approach required for managing this rare condition.